THE RELATION BETWEEN THE STERILITY EQUIPMENTS IN INFUSION TIME INSTITUTION AND FLOODBURY PRESENTATION IN FLAMBOYAN HOSPITAL ABDUL WAHAB SJAHRANIE SAMARINDA - Indah Nur Imamah (Jurnal Ilmu Kesehatan, 2019)
The nurse plays a significant role in caring for and helping someone from illness, wound. Hospital nursing service is a part that cannot be separated from health care as a whole, even as one factor determinant ao quality for service and image of the hospital in the eyes of society. To identify the relation between sterility of equipment on-time installation of in infusion with plaque incidence in the flamboyant space of disease in RSUD A.W SjahranieSamarinda Year 2016, This research uses descriptive correlative research design that is A research method undertaken to create descriptions or descriptions come to the situation that is being or done objectively, with a cross-sectional approach. According to SPO, the patient with happened phlebitis as much as one patient (25%), and accordingly, SPO did not occur phlebitis as many as seven patients (64%). While those that do not fit the SPO phlebitis occurred as many as three patients (75%) and no SPO did not occur phlebitis as many as 4patients (36%). That according to SPO, there was one patient phlebitis (25%), and accordingly soup There was no phlebitis of 7 patients (64%). While non-conforming SPO occurs phlebitis as much as three patients (75%) and no SPO did not occur phlebitis as many as four patients (36%).The results of this study found that.